Educational leadership and the management of change in higher education : implication of module-based teaching and learning at National University of Rwanda. - Nkurikiyumukiza, Phocas (My University, 2012)
On the assumption that leadership involves individuals with distinct qualities who take much ingenuity, energy and skills to trigger greater capacity in the organization for moving people towards organizational vision and goal achievement, the aim of this study is to identify and describe the leadership shown by managers and lecturers for the successful implementation of academic programme change at National University of Rwanda. That includes investigating the improvement of academic practice in the higher education institution while implementing change, i.e. introduction of the Module-Based Teaching and Learning (MBTL) methodology which is a new approach to schooling, as well as defining an appropriate leadership style needed for the management of this implementation. The research was carried out at National University of Rwanda as a case study and supported by the aid of interviews with faculty managers and lecturers as they are the main developers and users of teaching and learning programmes. Next, data collected were complemented by means of textual analysis. The findings revealed that the MBTL introduced at NUR as an innovation in academic practice was a top-down decision made by the policy makers without consultation with academic staffs and implemented without adequate preparation whereas they are the main actors in the implementation. Coupled with the change in the language of instruction from French to English and the lack of educational material required by the MBTL approach, the situation had an unenthusiastic impact on the engagement of NUR academics for accurate successful implementation. The overall conclusion is that inadequate management of the introduction of an educational change programme leads to misadoption and reluctance at best and resistance by the implementers at worst.
Keywords: Higher education; Educational leadership; Change management; Module-based teaching and learning; Academic improvement; Student outcome achievement; Curriculum reform; Innovation; Academic culture